High-performance delignification of invasive tree species wood with ionic liquid and deep eutectic solvent for the production of cellulose-based polyelectrolytes. Issue 7 (1st February 2022) - Almeida, Ricardo O.; Moreira, Adriana; Moreira, Daniela; Pina, Maria E.; Carvalho, Maria G. V. S.; Rasteiro, Maria G.; Gamelas, José A. F.
Abstract : Two cellulose-rich materials, with 6–7% of lignin, obtained from A. dealbata pretreatment with an ionic liquid or a deep eutectic solvent were used to produce cationic polyelectrolytes by a two-step reaction with sodium periodate and Girard's reagent T. Abstract : An efficient and eco-friendly process for lignocellulosic biomass fractionation is essential for the production of high value-added bioproducts from biomass. The present work aimed to obtain cellulose-rich materials from the wood of an invasive tree species ( Acacia dealbata ) using an appropriate choice of ionic liquids (ILs) and deep eutectic solvents (DESs), and of the processing conditions, for the subsequent production of cationic wood-based polyelectrolytes. In the pretreatment step, the 1-butyl-3-methylimidazolium methyl sulfate (IL) + H2 O and choline chloride + imidazole (DES) systems demonstrated a remarkable ability to remove lignin from acacia, reaching up to 92.4 and 90.2% of delignification, respectively. However, the DES pretreatment revealed to be more selective for lignin removal with lower cellulose losses (less than 15%) than the IL treatment (up to 30%) and less cellulose depolymerization. The hemicellulose was also removed but in a lesser extent with the DES treatment. Both systems could provide treated materials with a very high cellulose content (≥89%). Afterwards, cationic polyelectrolytes having a considerable content of quaternary ammonium groups (up to 3.6 mmol g −1 ) were obtained directly from the IL- and DES-pretreated woods. The treated woods, when used as raw materials for cationization reaction, allow to synthesize water-soluble polyelectrolytes with potential to be applied in wastewater treatment, pharmaceutical or cosmetic products.